Reliability Evaluation Method of AC/DC Hybrid Distribution Network Considering Voltage Source Converter Restoration Capability and Network Reconfiguration - Zhang, Lu; Yu, Shunjiang; Cai, Yongxiang; Tang, Wei; Cheng, Hongkai (Frontiers in Energy Research, 2022)
In AC/DC hybrid distribution network, the non-faulty areas can maintain uninterrupted power supply by adjusting the control mode of voltage source converter (VSC) after a fault. Additionally, the non-faulty areas can also be restored through network reconfiguration. To account for the impact of these two restoration methods on reliability accurately, this paper proposes a reliability evaluation method for AC/DC hybrid distribution network considering VSC restoration capability and network reconfiguration. Firstly, a restoration optimization model of AC/DC hybrid distribution network considering network reconfiguration and control modes of VSC is established, which can give full play to these two restoration methods while ensuring the radial constraints of the network. Then, the failure mode and effects analysis (FMEA) method is introduced and combined with the restoration optimization model to analyze the impact caused by faults on the network. Among them, the FMEA method is utilized to determine the network topology after fault isolation, and on this basis, the restoration optimization model is solved to obtain the outage time of loads in the network. Finally, the above work is combined with the sequential Monte Carlo method to evaluate the reliability of AC/DC hybrid distribution network to adequately simulate the fluctuation characteristics of distributed generation (DG) and load. Case study shows that the proposed method can accurately evaluate the reliability of AC/DC hybrid distribution network.